Moisture Reduction of Honey in Dehumidification and Evaporation Processes - Lastriyanto, Anang; Wibowo, Sasongko Aji; Erwan, Erwan; Jaya, Firman; Batoro, Jati; Masyithoh, Dewi; Lamerkabel, JSA (Universitas Negeri Malang, 2020)
The high water content of honey can lead to fermentation and accelerate the deterioration of honey. One way to prevent fermentation in honey is to reduce the water content of honey. There are several ways to reduce the water content of honey, namely through a dehumidifier and evaporation. This study aimed to examine the relationship of reduced water content towards time in between dehumidifier and evaporation processes. The research method uses an exponential equation model to determine the value of the constant (K). The constant value (K) is used to predict the rate of reduction in moisture content between the dehumidifier and evaporation processes. The results showed that the water content value after the dehumidifier and evaporation process had met the International Standard (SI) with a moisture content value of less than 19 %. The initial moisture content of honey before processing was 21.335 %, then after going through the process, the moisture content of honey in the dehumidifier and evaporation processes were 16.397 % and 14.625 %, respectively. The processing time required for decreasing the water content of honey in between dehumidification and evaporation processes also shows a very significantly difference; In the dehumidifier process, the process takes 720 min. While in the evaporation process, it is 50 min. The exponential equation to determine the constant value of K (1/min.) for the dehumidifier is y = 21.262e-0.00037x with the value of regression R2 = 0.9943. While the exponential equation formula to determine the constant value of K (1/min.) in the evaporation process is y = 21.961e-0.007x with the regression value represent R2 = 0.9262